Media and political opinion of young people in the city of Lima (conjuncture of April 5, 1992) - Quiroz-Velasco, María-Teresa (1994)
This article offers the results of a research work carried out among young people in the city of Lima about their opinion regarding the national situation, political institutions and the media. The general intention is to analyze the way in which the media contribute or participate in the presentation of a certain policy scenario.